Social-Ambient traits of the hydrographic basin of the River Ribeira de Iguape - Antuniassi, Maria Helena Rocha; Reismann, Lia (Cadernos CERU, 2001)
The hydrographic basin of the river Ribeira de Iguape is constituted by thirty eight municipalities of the state of São Paulo and Paraná: it begins at the urban peripheries of two Brazilian metropolis, crosses through extended areas of less modernised agriculture and cattle raising, and ends at a lagoon complex, partially occupied and explored. Several plans have been outlined for this region, but not always implemented. The development policies of the late decades, especially in the part of São Paulo, were not successfull in attaining significant changes in economical and population traits that could promote an impulse of the same sort as of the others regions, of the state. Presently policies of environmental protection of the nature reserves and policies of social-economical develpment are being confronted in order to revert the stagnation picture verified in big parts of the focused area. So the study discusses the present characteristics of the area and some of its possibilities of development.